Pengaruh asal populasi dan komposisi media terhadap keberhasilan stek pucuk pulai darat (alstonia angustiloba Miq) - Mashudi Mashudi (Center for Forest Biotechnology and Tree Improvement (CFBTI), 2011)
The aims of this experiment was to investigate effect of population sources and media composition toward shoot cutting growth of Alsonia angusiloba Miq. From two sprouts age. This experiment was arranged in completely randomized design with factorial setting. The research used 2 factors. i.e. population source (Banten,Pendopo,Lubuk Linggau and Solok) and media compositions (sand, cocopeat, husk charcoal. Sand : husk charcoal (4;1) and sand cocopeat (4 :1). The result showed that interaction of population source and media composition did not give any significant effect on parameters measured. Lubuk Linggau population produced the best of rooting percentage (31.19 %) from 3 month sprouts age and Pendopo population produced the best of rooting percentage (65.52 %), number of root (5.50) and length of root (2.79 cm) from 5 month sprouts age. Sand : cocopeat (4:1) media produced the best of number of root (4.14) and length of root (2.41 cm) from 3 mionth sprouts age. Sand media produced the best of rooting percentage (70.42 %), number of sprout (5.27) and length of sprout (2.82 cm) from spouts age. Rooting percentage, number and length of roots tended to increase from 3 month sprouts age to month sprouts age.